On the optimal object orientation in additive manufacturing - Pereira, Sérgio (2018)
Additive manufacturing (AM) has emerged in the last decades as an alternative to traditional subtractive and forming manufacturing processes. AM is a process where 3D objects are built by adding material in consecutive layers. Typical AM is characterized by four processing stages: model orientation, creation of supports, slicing, and path planning. In this paper, we will focus on how to use mathematical optimization to address some limitations that arise from the model orientation, creation of supports, and slicing processing stages. Model orientation and creation of supports are usually related, since the best orientation of the object to be built can result in lower building time and lower need for creation of supports, leading to an improvement of the surface quality. Slicing comprises the object division by layers and the major difficulty is the staircase effect, which becomes more critical for objects with high slopes and curvatures, resulting in high roughness surfaces. In this paper, we show how to take advantage of a state-of-the-art optimization solver to optimize object building orientation and the need for supports generation in additive manufacturing, thus leading to better object surface accuracy and smoothness.